2020
DOI: 10.2147/ott.s251436
|View full text |Cite
|
Sign up to set email alerts
|

<p>CircHIPK3 Promotes Clear Cell Renal Cell Carcinoma (ccRCC) Cells Proliferation and Metastasis via Altering of miR-508-3p/CXCL13 Signal</p>

Abstract: Introduction Accumulating evidence has demonstrated that circular RNAs (circRNAs) play a key role in the tumorigenesis of various types of cancers, including clear cell renal cell carcinoma (ccRCC). Materials and Methods Reverse transcription-quantitative polymerase chain reaction was used to detect the expression of circRNA homeodomain interacting protein kinase 3 (circHIPK3) and microRNAs (miRNAs), including miR-508-3p. The clinical measurement of circHIPK3 was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Studies have confirmed that circHIPK3 is located in the cytoplasm. 15 circRNA competitively binds to miRNAs and regulates the expression of downstream target genes when it is located in the cytoplasm. 16 MicroRNAs (miRNAs) are a class of small noncoding RNAs, including 20∼25 nucleotides, which regulate the expression levels of target genes by binding to the 3′-untranslated region (UTR) of mRNAs, degrading mRNAs, or inhibiting their translation process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that circHIPK3 is located in the cytoplasm. 15 circRNA competitively binds to miRNAs and regulates the expression of downstream target genes when it is located in the cytoplasm. 16 MicroRNAs (miRNAs) are a class of small noncoding RNAs, including 20∼25 nucleotides, which regulate the expression levels of target genes by binding to the 3′-untranslated region (UTR) of mRNAs, degrading mRNAs, or inhibiting their translation process.…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial vessels, circ-CCAC1 up-regulates SH3GL2 by sequestering EZH2, thus reducing intercellular junction protein levels and increasing cell leakiness [48]. circRNAHIPK3 derived from exon 2 of HIPK3 gene is highly expressed in many types of cancer, including glioma [49], prostate cancer [50], breast cancer [51], colorectal cancer [52] and renal cancer [53]. Through screening of 424 miRNAs, 9 miRNAs showed great suppressive ability on the HIPK3 exon 2.…”
Section: Circrnas In Cancersmentioning
confidence: 99%
“…Li et al ( 107 ) found that the overexpression of circHIPK3 significantly inhibited RC cell invasion and migration in vitro , and it repressed proliferation of RC cells in vitro and in vivo . Additionally, another study by Han et al ( 108 ) demonstrated that circHIPK3 promoted clear cell RC cell proliferation and migration by altering miR-5083p/CXCL13 signaling, highlighting a potentially novel target for the molecular treatment of clear cell RC.…”
Section: Circhipk3 and Human Diseasesmentioning
confidence: 99%